2015
DOI: 10.1094/pdis-01-15-0061-re
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of ‘Candidatus Phytoplasma cynodontis’ Based on 16S rRNA and groEL Genes and Identification of a New Subgroup, 16SrXIV-C

Abstract: ‘Candidatus Phytoplasma cynodontis’ is widespread in bermudagrass and has only been found in monocotyledonous plants. Molecular studies carried out on strains collected in Italy, Serbia, and Albania enabled verification of molecular variability in the 16S ribosomal RNA (rRNA) gene. Based on restriction fragment length polymorphism and sequence analyses, the strains from Serbia were clearly differentiated from all others and assigned to a new ribosomal DNA (rDNA) subgroup designated as 16SrXIV-C. A system for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The present study confirms previously published work (Dumonceaux et al , 2014; Mitrović et al , 2011, 2015) showing the capability of cpn60 UT sequences to act as an additional marker to differentiate phytoplasmas. Strains that are closely related based on 16S rRNA gene sequence classification were differentiated as members of new subgroups, contributing to a better identification of the strains.…”
Section: Differentiating Phytoplasmas Based On Cpn60 Ut Sequencessupporting
confidence: 92%
See 2 more Smart Citations
“…The present study confirms previously published work (Dumonceaux et al , 2014; Mitrović et al , 2011, 2015) showing the capability of cpn60 UT sequences to act as an additional marker to differentiate phytoplasmas. Strains that are closely related based on 16S rRNA gene sequence classification were differentiated as members of new subgroups, contributing to a better identification of the strains.…”
Section: Differentiating Phytoplasmas Based On Cpn60 Ut Sequencessupporting
confidence: 92%
“…Altogether, after trimming the cpn60 UT sequence from the five completely sequenced phytoplasma genomes (Andersen et al , 2013; Bai et al , 2006; Kube et al , 2008; Oshima et al , 2013; Tran-Nguyen et al , 2008), from the draft genome belonging to the group 16SrII-A, strain PnWB (Chung et al , 2013) and 16SrIX-B strain SA213 (Quaglino et al , 2015), from the cpn60 sequences reported by Mitrović et al (2011) for members of the group 16SrI, and members of the group 16SrXIV (Mitrović et al , 2015), from the 3.6 kb DNA fragments obtained by Kakizawa et al (2006), and the sequences previously obtained by our group, we had 96 cpn60 UT sequences in this study.…”
Section: Differentiating Phytoplasmas Based On Cpn60 Ut Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kenya (Obura et al 2010) Italy, Albania and Serbia (Mitrović et al 2015) and Saudi Arabia (Omar 2016) .…”
Section: Resultsmentioning
confidence: 99%
“…Bermuda grass white leaf (BGWL), first described in Taiwan, is a destructive phytoplasmal disease of Bermuda grass caused by the phytoplasma group (16SrXIV) and characterized by whitening of the leaves and shortening of the stolons (Chen et al 1972;Obura et al 2010). BGWL disease is reported in many countries including Singapore (Koh et al 2008), Italy (Marcone & Ragozzino 1997), Iran (Salehi et al 2009), Cuba (Arocha et al 2005), Australia (Padovan et al 1999;Tran-Nguyen et al 2000), Turkey (Çağlar et al 2013), Sudan (Dafalla & Cousin 1988), Thailand (Sunpapao 2014), India (Rao et al 2007;Snehi et al 2008;Kumar et al 2015), Malaysia (Nejat et al 2009;Naderali et al 2013), Myanmar (Win et al 2013), Kenya, Tanzania and Uganda (Asudi et al 2015), and Serbia and Albania (Mitrović et al 2015). Phytoplasmas, wall-less prokaryotes, classified in the Class Mollicutes, Order Acholeplasmatales and genus Candidatus are uncultivable (Xiaodong et al 2006).…”
Section: Introductionmentioning
confidence: 99%